Effect of Extrinsic Job Satisfaction Hygiene Factors and Intrinsic Job Satisfaction Motivation on Turnover Intention - Rohmawan Adi Pratama; Muhammad Japar; Purwati Purwati; Filda Khoirun Nikmah; Ignatius Soni Kurniawan (Kuras Institute, 2023)
The relationship between extrinsic job satisfaction and turnover intentions is significant in research concerning employee behavior and organizational dynamics. Outside satisfaction factors, commonly labeled as hygiene factors, significantly negatively impact employees' propensity to consider leaving their positions. This study examines (1) the correlation of extrinsic job satisfaction on turnover intention and (2) the negative effect of intrinsic job satisfaction on turnover intention. To test the hypothesis, this study used a quantitative correlational approach to determine the relationship between two or more variables. This research used a questionnaire of 120 respondents at the University of Muhammadiyah Magelang. Based on the data processing results, the first hypothesis testing shows that extrinsic job satisfaction negatively and significantly affects turnover intention (β = -0.267; t = -4.951; p = .000 <.005). The second hypothesis testing results show that intrinsic job satisfaction has a negative and significant effect on turnover intention (β = -.098; t = -2,677; p = .009 <.005).